Internet of Things (IoT) and cyber security in the control of electrical energy systems: A review - Kocak, Yusuf; Abut, Nurettin (Trends in Computer Science and Information Technology, 2024)
This article provides an assessment of the use of Internet of Things (IoT) technology in the control of electrical energy power systems and its cybersecurity risks. Electrical energy systems are complex and critical infrastructures today, and effective management and control of these systems are of great importance. The use of IoT technology in electrical energy systems allows these systems to become more efficient, flexible, and intelligent. However, the use of this technology also brings various cyber security risks. While this article examines the applications of IoT in power systems, it also focuses on how these systems can be protected against cybersecurity vulnerabilities.